Anomalous time delays and quantum weak measurements in optical micro-resonators - M. Asano (Nature Portfolio, 2016)
Interference of linear plane waves produces non-trivial phenomena in both classical and quantum wave systems. Here, the authors describe and observe anomalously large time delays and frequency shifts in the resonant inelastic scattering of a 1D wave packet near a zero of the scattering coefficient.